SYNTACTIC AMBIGUITY FOUND IN BUSINESS HEADLINES OF THE NEW YORK TIMES - Siti Nurfadilah (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2022)
This study is conducted to analyze the syntactic ambiguity in business headlines on the news of The New York Times. This study aimed at explaining: (1) the ambiguity in the tree diagram. (2) The suitability of the headlines with the content of the news in The New York Times. The data source is the online news in The New York Times. The data are collected by (1)Opening the Google Chrome app, (2) Accessing the official website https://nytimes.com, (3) Choosing the column